Enhanced Corrosion Resistance and Local Therapy from Nano-Engineered Titanium Dental Implants - Tianqi Guo; Jean-Claude Scimeca; Sašo Ivanovski; Elise Verron; Karan Gulati (MDPI AG, 2023)
Titanium is the ideal material for fabricating dental implants with favorable biocompatibility and biomechanics. However, the chemical corrosions arising from interaction with the surrounding tissues and fluids in oral cavity can challenge the integrity of Ti implants and leach Ti ions/nanoparticles, thereby causing cytotoxicity. Various nanoscale surface modifications have been performed to augment the chemical and electrochemical stability of Ti-based dental implants, and this review discusses and details these advances. For instance, depositing nanowires/nanoparticles via alkali-heat treatment and plasma spraying results in the fabrication of a nanostructured layer to reduce chemical corrosion. Further, refining the grain size to nanoscale could enhance Ti implants' mechanical and chemical stability by alleviating the internal strain and establishing a uniform TiO2 layer. More recently, electrochemical anodization (EA) has emerged as a promising method to fabricate controlled TiO2 nanostructures on Ti dental implants. These anodized implants enhance Ti implants' corrosion resistance and bioactivity. A particular focus of this review is to highlight critical advances in anodized Ti implants with nanotubes/nanopores for local drug delivery of potent therapeutics to augment osseo- and soft-tissue integration. This review aims to improve the understanding of novel nano-engineered Ti dental implant modifications, focusing on anodized nanostructures to fabricate the next generation of therapeutic and corrosion-resistant dental implants. The review explores the latest developments, clinical translation challenges, and future directions to assist in developing the next generation of dental implants that will survive long-term in the complex corrosive oral microenvironment.